Scribal habits in early Greek New Testament papyri - Royse, James Ronald. (New Testament Tools, Studies and Documents, 2008)
In textual criticism, the 'scribal habits' in a manuscript (tendencies to make various sorts of changes) must be known in order to evaluate its testimony. Colwell analyzed the scribal habits in P45, P66, and P75, by examining their singular readings. This book expands on Colwell's work by studying P45, P46, P47, P66, P72, and P75, the six most extensive early New Testament manuscripts. All the singular readings in these papyri are studied along with all the corrections. The results, which incorporate many revised readings of these papyri, make possible the more precise use of these papyri in textual criticism. Among the important discoveries is that the general tendency of these early scribes was to omit rather than to add.